URGENSI FIQH KONTEMPORER DALAM MENGATUR CROWDFUNDING DI MASYARAKAT MODERN - Azizatur Rosyidah; Isroqunnajah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The development of digital technology has driven vorious innovations in the financial sector, including crowdfunding as an alternative funding instrument that has gained increasing attention in Indonesia. Although offering ease of access and inclusivity, modern crowdfunding practices also present legal and ethical challenges, particularly regarding compliance with Islamic principles. This issue is crucial given that Indonesia has the largest Muslim population in the world, thus requiring appropriate regulations and a contemporary fiqh framework to govern such practices. This study aims to analyze the urgency of contemporary fiqh in regulating crowdfunding within modern society by examining the suitability of its mechanisms, contracts (akad), and implementation models from a sharia perspective. This research employs a qualitative descriptive method with a library research approach, utilizing sources such as books, academic journals, OJK regulations, DSN-MUI fatwas, and previous studies as the basis of analysis. The analytical technique used is content analysis to identify and synthesize various concepts and findings from the literature. The results show that sharia-based crowdfunding can serve as an ethical, inclusive, and sharia-compliant funding instrument when grounded in the principles of ta’awun, trustworthiness, justice, and the avoidance of riba, gharar, and maysir. Additionally, the regulatory framework involving OJK, DSN, and DPS plays a crucial role in ensuring sharia compliance and safeguarding all parties involved. This study concludes that integrating contemporary fiqh into crowdfunding regulation is essential to establishing an ethical and sustainable digital financial ecosystem.